Learnership: Invest in Teachers, Focus on Learning, and Put Test Scoresin Perspective. - Toll, Cathy A. (Corwin, A SAGE Publications Company, 2012)
Do you feel bogged down by endless administrative tasks? Do you wish you could focus more on what truly matters--learning? "Learnership" provides both insight and solutions for moving past the distractions and becoming a learning leader. Cathy Toll illustrates this transformational process through activities and focused "learning conversations." Toll uses supported actions, theory and research, real-life stories, and narrative bibliography to explain how the practice of learnership can be implemented on a daily basis. This book offers: (1) Practices to help teachers improve their effectiveness using problem-solving techniques; (2) More effective ways to approach data, testing, and accountability; and (3) Strategies for supporting Professional Learning Teams (plt) and educational coaches. "Learnership" is an invaluable resource for principals and teachers in school-based leadership roles, or anyone who wishes to focus on school improvement and their own personal growth as a leader in education